Analysis of the common complications and recurrence-related factors of superior parasagittal sinus meningioma - Chen, Wei-Wei; Wang, Yong; Hu, Yang-Chun; Zhao, Yuan-Li (Frontiers in Surgery, 2023)
Objectives: Parasagittal meningioma resection is prone to postoperative complications and tumor recurrence because the tumor invades the superior sagittal sinus. This study aimed to clarify the incidence of perioperative complications and the recurrence of superior sagittal paranasal meningiomas and explored potential predictors in this context. Methods: The study retrospectively reviewed the clinical, imaging, and follow-up data of parasagittal meningiomas among patients who underwent microsurgical resection in the authors’ institution from January 2008 to December 2017. Univariate and multivariate logistic regression analyses were conducted to explore independent predictors of perioperative complications and tumor recurrence. Results: A total of 212 parasagittal meningioma patients were included in this study. The incidence of perioperative complications was 23.6% (50/212), and perioperative death occurred in 6 (2.8%) patients. In univariate and multivariate logistic regression analyses of perioperative complications, peritumoral edema <1 cm (odds ratio [OR] 0.465, 95% confidence interval [CI] 0.228–0.950, P = 0.036) and the Sindou grade (OR 1.870, 95% CI 1.147–3.048, 0.036) were independent predictors. After an average of 83 (39–154) months of clinical follow up among the living 206 patients, 22 (10.7%) patients showed tumor recurrence. In univariate and multivariate logistic regression analyses of tumor recurrence, perioperative tumor pathological grade (OR:3.574,CI:1.355-9.424,P:0.010), and the Sindou grade (OR:3.183,CI:1.621-6,250,P:0.001) were independent predictors. Conclusions: Peritumoral edema <1 cm and Sindou grade were the independent predictors of perioperative complications, and perioperative tumor pathological grade and the Sindou grade were the independent predictors of tumor recurrence. The part of the parasagittal meningioma involving the sinus wall should be actively removed to the largest degree possible to reduce the recurrence rate.